A kind of graphene negative ion water-based paint and its production process

Through the combination of graphene liquid and negative ionic liquid, the problems of the antibacteriality of existing water-based coatings are solved, and the problem of the difficulty in coordinating the improvement of purification effects and poor stain resistance are achieved, and the coordination of antibacteriality and purification and adsorption effects are improved and the resistance to resistance of antibacteriality and purification and adsorption effects are achieved. Enhanced performance of dirty.

CN118931286BInactive Publication Date: 2025-02-25TIANJIN DINGSHENG GRAPHENE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411231686.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antibacterial and antibacterial effects of existing water-based coatings are not long-lasting, the purification effect is difficult to coordinate and improve, and the stain resistance is poor, which limits the efficiency of the product.

Method used

Graphene liquid is combined with negative ionic raw liquid, emulsion, additives, pigments, nano-silver powder, diatomaceous earth powder and other raw materials. Through the combination of graphene heat treatment and regulation treatment agent, negative ionic aqueous coating is formed to enhance antibacterial, adsorption purification and Stain resistance.

Benefits of technology

The coordination of antibacterial properties and purification and adsorption effects is achieved, the product's stain resistance is enhanced, and the use efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005026349990000111
    Figure BDA0005026349990000111
  • Figure BDA0005026349990000121
    Figure BDA0005026349990000121
Patent Text Reader

Abstract

The invention discloses a graphene anion water-based paint and a production process thereof, wherein the graphene anion water-based paint comprises the following raw materials in parts by weight: 5-10 parts of graphene liquid, 45-50 parts of anion stock solution, 175-185 parts of emulsion, 4-7 parts of auxiliary agent, 45-50 parts of pigment, 5-10 parts of nano silver powder, 5-10 parts of diatomite powder, and 470-490 parts of deionized water. The anion water-based paint of the present invention adopts graphene liquid to coordinate the anion stock solution, emulsion, auxiliary agent, pigment, nano silver powder, and diatomite powder raw materials to be mutually combined and blended, and the anion stock solution obtained by combining tourmaline powder, potassium tungstate powder and water releases anions to form anion efficacy, and nano silver improves the antibacterial property of the product and the purification adsorption effect of diatomite to realize air, and graphene liquid is used to coordinate synergy with kaolin agent to enhance the antibacterial and adsorption purification coordination of the product, and the anti-fouling performance effect of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based coatings, and in particular to a graphene negative ion water-based coating and a production process thereof. Background Art

[0002] After many years of development, water-based emulsion paints have made breakthroughs in health and environmental protection. However, although negative ion paints can provide negative oxygen ion function, the antibacterial effect of the product is not long-lasting and it is difficult to achieve a purification effect. The antibacterial effect is not long-lasting, the purification effect is difficult to coordinate and improve, and the product has poor stain resistance, which further limits the efficiency of the product. Summary of the Invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a graphene negative ion water-based coating and a production process thereof to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solutions:

[0005] The present invention provides a graphene negative ion water-based paint, which comprises the following raw materials in parts by weight:

[0006] 5-10 parts of graphene liquid, 45-50 parts of negative ion stock solution, 175-185 parts of emulsion, 4-7 parts of additives, 45-50 parts of pigment, 5-10 parts of nano silver powder, 5-10 parts of diatomaceous earth powder, and 470-490 parts of deionized water.

[0007] Preferably, the negative ion stock solution is obtained by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3;

[0008] The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%;

[0009] The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

[0010] Preferably, the method for preparing the graphene liquid is:

[0011] S01: The graphene is first heat treated at 135-145°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at this temperature for 2 minutes, and finally cooled to 50°C at a rate of 1-3°C / min, and continued to be kept at this temperature;

[0012] S02: 2-5 parts of nano-silica, 1-3 parts of silane coupling agent and 2-5 parts of yttrium nitrate solution are fully mixed, and then 1-2 parts of stearic acid and 0.25-0.35 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent;

[0013] S03: The graphene and the conditioning agent kept warm in S01 are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioned graphene agent;

[0014] S04: The adjusted graphene agent, chitosan solution and phosphate buffer solution are mixed thoroughly in a weight ratio of 3:5:1 to obtain a graphene solution.

[0015] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%; and the pH value of the phosphate buffer solution is 5.5.

[0016] Preferably, the silane coupling agent is silane coupling agent KH560.

[0017] Preferably, the preparation method of the calcium sulfate whisker modifier is:

[0018] irradiating the calcium sulfate whiskers in a proton irradiation box for 2-5 minutes, and then placing the irradiated calcium sulfate whiskers in a sodium silicate solution having a mass fraction of 2-5 times the amount thereof and stirring the solution to obtain a sodium silicate-adjusted calcium sulfate whisker agent.

[0019] Lanthanum oxide accounting for 4-7% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, nano-silica sol accounting for 2-5% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, and sodium dodecylbenzenesulfonate accounting for 4-8% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate are added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture is ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After thorough ball-milling, the mixture is washed with water and dried to obtain a calcium sulfate whisker modifier.

[0020] Preferably, the irradiation power in the proton irradiation box is 220-230W.

[0021] Preferably, the graphene negative ion water-based coating further comprises 2-5 parts by weight of kaolin agent;

[0022] The preparation method of kaolin agent is:

[0023] S101: calcining kaolin at 300°C for 2 h, then cooling to 125°C at a rate of 2-5°C / min, holding for 20 min, and finally air-cooling to room temperature;

[0024] S102: air-cooling kaolin to room temperature and mixing it with sodium lignin sulfonate solution in an amount of 3-5 times the total amount of kaolin, then adding carboxymethyl cellulose in an amount of 10-15% of the total amount of kaolin and citric acid in an amount of 2-5% of the total amount of kaolin and continuing to mix thoroughly, finally washing with water and drying to obtain a kaolin agent.

[0025] Preferably, the mass fraction of the sodium lignin sulfonate solution is 10-15%.

[0026] The present invention also provides a preparation process of a graphene negative ion water-based paint, comprising the following steps: stirring and mixing the raw materials thoroughly to obtain the negative ion water-based paint of the present invention.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The negative ion water-based paint of the present invention adopts graphene liquid, negative ion stock solution, emulsion, auxiliary agent, pigment, nano silver powder and diatomaceous earth powder raw materials, which are combined and blended with each other. The negative ion stock solution obtained by mixing tourmaline powder, potassium tungstate powder and water releases negative ions to form negative ion efficacy, while nano silver improves the antibacterial property of the product and diatomaceous earth realizes the air purification and adsorption effect. The graphene liquid is combined with kaolin agent for coordinated synergy, thereby enhancing the antibacterial, adsorption and purification coordination of the product and the anti-fouling performance of the product. The graphene in the graphene liquid is heat-treated at 135-145°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept warm for 2 minutes, and finally cooled to 50°C at a rate of 1-3°C / min to optimize the active efficiency of the graphene. Then, nano silicon dioxide, silane coupling agent, yttrium nitrate solution, stearic acid and calcium sulfate whisker modifier are mixed, and the raw materials are mixed to form a negative ion product. The mutual adjustment and assistance between them, the graphene is coordinated with nano-silica and calcium sulfate whisker modifiers, and the interfacial effect between the raw materials of the system is enhanced in the flaky graphene distribution system. At the same time, the antibacterial durability, purification adsorption and stain resistance of the product are enhanced by nano-silica and calcium sulfate whiskers with high specific surface area. At the same time, chitosan solution and phosphate buffer solution are used to assist each other, and the formed graphene liquid is better dispersed in the system. At the same time, the kaolin agent is distributed in the kaolin lamellar structure system to enhance the adsorption and purification effect of the system. The kaolin is calcined at 300°C for 2h, then cooled to 125°C at a rate of 2-5°C / min, kept warm for 20min, and finally air-cooled to room temperature. It is then blended with sodium lignin sulfonate solution, carboxymethyl cellulose and citric acid to improve the kaolin agent. The obtained kaolin agent can better coordinate and synergize with the graphene liquid, and the product performance is further improved. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0030] A graphene negative ion water-based paint according to this embodiment includes the following raw materials in parts by weight:

[0031] 5-10 parts of graphene liquid, 45-50 parts of negative ion stock solution, 175-185 parts of emulsion, 4-7 parts of additives, 45-50 parts of pigment, 5-10 parts of nano silver powder, 5-10 parts of diatomaceous earth powder, and 470-490 parts of deionized water.

[0032] The negative ion stock solution of this embodiment is prepared by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3 to obtain a negative ion stock solution;

[0033] The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%;

[0034] The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

[0035] The preparation method of the graphene liquid of this embodiment is:

[0036] S01: The graphene is first heat treated at 135-145°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at this temperature for 2 minutes, and finally cooled to 50°C at a rate of 1-3°C / min, and continued to be kept at this temperature;

[0037] S02: 2-5 parts of nano-silica, 1-3 parts of silane coupling agent and 2-5 parts of yttrium nitrate solution are fully mixed, and then 1-2 parts of stearic acid and 0.25-0.35 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent;

[0038] S03: The graphene and the conditioning agent kept warm in S01 are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioned graphene agent;

[0039] S04: The adjusted graphene agent, chitosan solution and phosphate buffer solution are mixed thoroughly in a weight ratio of 3:5:1 to obtain a graphene solution.

[0040] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 4-7%; and the pH value of the phosphate buffer solution is 5.5.

[0041] The silane coupling agent in this embodiment is silane coupling agent KH560.

[0042] The preparation method of the calcium sulfate whisker modifier of the present embodiment is:

[0043] irradiating the calcium sulfate whiskers in a proton irradiation box for 2-5 minutes, and then placing the irradiated calcium sulfate whiskers in a sodium silicate solution having a mass fraction of 2-5 times the amount thereof and stirring the solution to obtain a sodium silicate-adjusted calcium sulfate whisker agent.

[0044] Lanthanum oxide accounting for 4-7% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, nano-silica sol accounting for 2-5% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, and sodium dodecylbenzenesulfonate accounting for 4-8% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate are added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture is ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After thorough ball-milling, the mixture is washed with water and dried to obtain a calcium sulfate whisker modifier.

[0045] The irradiation power in the proton irradiation box of this embodiment is 220-230W.

[0046] The graphene negative ion water-based coating of this embodiment further comprises 2-5 parts by weight of kaolin agent;

[0047] The preparation method of kaolin agent is:

[0048] S101: calcining kaolin at 300°C for 2 h, then cooling to 125°C at a rate of 2-5°C / min, holding for 20 min, and finally air-cooling to room temperature;

[0049] S102: air-cooling kaolin to room temperature and mixing it with sodium lignin sulfonate solution in an amount of 3-5 times the total amount of kaolin, then adding carboxymethyl cellulose in an amount of 10-15% of the total amount of kaolin and citric acid in an amount of 2-5% of the total amount of kaolin and continuing to mix thoroughly, finally washing with water and drying to obtain a kaolin agent.

[0050] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10-15%.

[0051] The preparation process of a graphene negative ion water-based coating of the present embodiment comprises the following steps: stirring and mixing the raw materials thoroughly to obtain the negative ion water-based coating of the present invention.

[0052] Example 1.

[0053] A graphene negative ion water-based paint according to this embodiment includes the following raw materials in parts by weight:

[0054] 5 parts of graphene liquid, 45 parts of negative ion stock solution, 175 parts of emulsion, 4 parts of additives, 45 parts of pigment, 5 parts of nano silver powder, 5 parts of diatomaceous earth powder, and 470 parts of deionized water.

[0055] The negative ion stock solution of this embodiment is prepared by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3 to obtain a negative ion stock solution;

[0056] The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%;

[0057] The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

[0058] The preparation method of the graphene liquid of this embodiment is:

[0059] S01: The graphene was first heat treated at 135°C for 5 min, then heated to 300°C at a rate of 2°C / min, kept at this temperature for 2 min, and finally cooled to 50°C at a rate of 1°C / min, and continued to be kept at this temperature;

[0060] S02: 2 parts of nano-silica, 1 part of silane coupling agent and 2 parts of yttrium nitrate solution are fully mixed, and then 1 part of stearic acid and 0.25 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent;

[0061] S03: The graphene and the conditioning agent kept warm in S01 are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioned graphene agent;

[0062] S04: The adjusted graphene agent, chitosan solution and phosphate buffer solution are mixed thoroughly in a weight ratio of 3:5:1 to obtain a graphene solution.

[0063] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the chitosan solution is 4%; and the pH value of the phosphate buffer solution is 5.5.

[0064] The silane coupling agent in this embodiment is silane coupling agent KH560.

[0065] The preparation method of the calcium sulfate whisker modifier of the present embodiment is:

[0066] irradiating the calcium sulfate whiskers in a proton irradiation box for 2 minutes, and then placing the irradiated calcium sulfate whiskers in a sodium silicate solution having a mass fraction of 5% and stirring them evenly to obtain a sodium silicate-adjusted calcium sulfate whisker agent;

[0067] Lanthanum oxide (4% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate), nano-silica sol (2% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate) and sodium dodecylbenzenesulfonate (4% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate) were added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture was ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After thorough ball-milling, the mixture was washed with water and dried to obtain a calcium sulfate whisker modifier.

[0068] The irradiation power in the proton irradiation box of this embodiment is 220W.

[0069] The graphene negative ion water-based coating of this embodiment further includes 2 parts by weight of kaolin agent;

[0070] The preparation method of kaolin agent is:

[0071] S101: calcining kaolin at 300°C for 2 h, then cooling to 125°C at a rate of 2°C / min, holding for 20 min, and finally air-cooling to room temperature;

[0072] S102: The kaolin cooled to room temperature is mixed thoroughly with a sodium lignin sulfonate solution 3 times the total amount of the kaolin, and then carboxymethyl cellulose 10% of the total amount of the kaolin and citric acid 2% of the total amount of the kaolin are added and the mixture is further mixed thoroughly. Finally, the mixture is washed with water and dried to obtain a kaolin agent.

[0073] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10%.

[0074] The preparation process of a graphene negative ion water-based coating of the present embodiment comprises the following steps: stirring and mixing the raw materials thoroughly to obtain the negative ion water-based coating of the present invention.

[0075] Example 2.

[0076] A graphene negative ion water-based paint according to this embodiment includes the following raw materials in parts by weight:

[0077] 10 parts of graphene liquid, 50 parts of negative ion stock solution, 185 parts of emulsion, 7 parts of additives, 50 parts of pigment, 10 parts of nano silver powder, 10 parts of diatomaceous earth powder, and 490 parts of deionized water.

[0078] The negative ion stock solution of this embodiment is prepared by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3 to obtain a negative ion stock solution;

[0079] The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%;

[0080] The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

[0081] The preparation method of the graphene liquid of this embodiment is:

[0082] S01: The graphene was first heat treated at 145°C for 10 min, then heated to 300°C at a rate of 5°C / min, kept at this temperature for 2 min, and finally cooled to 50°C at a rate of 3°C / min and continued to be kept at this temperature.

[0083] S02: 5 parts of nano-silica, 3 parts of silane coupling agent and 5 parts of yttrium nitrate solution are fully mixed, and finally 2 parts of stearic acid and 0.35 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent;

[0084] S03: The graphene and the conditioning agent kept warm in S01 are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioned graphene agent;

[0085] S04: The adjusted graphene agent, chitosan solution and phosphate buffer solution are mixed thoroughly in a weight ratio of 3:5:1 to obtain a graphene solution.

[0086] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 7%; and the pH value of the phosphate buffer solution is 5.5.

[0087] The silane coupling agent in this embodiment is silane coupling agent KH560.

[0088] The preparation method of the calcium sulfate whisker modifier of the present embodiment is:

[0089] irradiating the calcium sulfate whiskers in a proton irradiation box for 5 minutes, and then placing the irradiated calcium sulfate whiskers in a sodium silicate solution having a mass fraction of 5% and stirring them evenly to obtain a sodium silicate-adjusted calcium sulfate whisker agent;

[0090] Lanthanum oxide accounting for 7% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, nano-silica sol accounting for 5% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, and sodium dodecylbenzenesulfonate accounting for 8% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate are added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture is ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After thorough ball-milling, the mixture is washed with water and dried to obtain a calcium sulfate whisker modifier.

[0091] The irradiation power in the proton irradiation box of this embodiment is 230W.

[0092] The graphene negative ion water-based coating of this embodiment further includes 5 parts by weight of kaolin agent;

[0093] The preparation method of kaolin agent is:

[0094] S101: calcining kaolin at 300°C for 2 h, then cooling to 125°C at a rate of 5°C / min, holding for 20 min, and finally air-cooling to room temperature;

[0095] S102: The kaolin cooled to room temperature is mixed thoroughly with a sodium lignin sulfonate solution of 5 times the total amount of the kaolin, and then carboxymethyl cellulose of 15% of the total amount of the kaolin and citric acid of 5% of the total amount of the kaolin are added and the mixture is further mixed thoroughly. Finally, the mixture is washed with water and dried to obtain a kaolin agent.

[0096] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 15%.

[0097] The preparation process of a graphene negative ion water-based coating of the present embodiment comprises the following steps: stirring and mixing the raw materials thoroughly to obtain the negative ion water-based coating of the present invention.

[0098] Example 3.

[0099] A graphene negative ion water-based paint according to this embodiment includes the following raw materials in parts by weight:

[0100] 7.5 parts of graphene liquid, 47.5 parts of negative ion stock solution, 180 parts of emulsion, 5.5 parts of additives, 47.5 parts of pigment, 7.5 parts of nano silver powder, 7.5 parts of diatomaceous earth powder, and 480 parts of deionized water.

[0101] The negative ion stock solution of this embodiment is prepared by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3 to obtain a negative ion stock solution;

[0102] The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%;

[0103] The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

[0104] The preparation method of the graphene liquid of this embodiment is:

[0105] S01: The graphene was first heat treated at 140°C for 7.5 min, then heated to 300°C at a rate of 3.5°C / min, kept at this temperature for 2 min, and finally cooled to 50°C at a rate of 2°C / min and continued to be kept at this temperature.

[0106] S02: 3.5 parts of nano-silica, 2 parts of silane coupling agent and 3.5 parts of yttrium nitrate solution are fully mixed, and then 1.5 parts of stearic acid and 0.30 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent;

[0107] S03: The graphene kept warm in S01 and the conditioning agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioned graphene agent;

[0108] S04: The adjusted graphene agent, chitosan solution and phosphate buffer solution are mixed thoroughly in a weight ratio of 3:5:1 to obtain a graphene solution.

[0109] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 5.5%; and the pH value of the phosphate buffer solution is 5.5.

[0110] The silane coupling agent in this embodiment is silane coupling agent KH560.

[0111] The preparation method of the calcium sulfate whisker modifier of the present embodiment is:

[0112] irradiating the calcium sulfate whiskers in a proton irradiation box for 3.5 minutes, and then placing the irradiated calcium sulfate whiskers in a sodium silicate solution having a mass fraction of 3.5 times that of 5% and stirring evenly to obtain a sodium silicate-adjusted calcium sulfate whisker agent;

[0113] Lanthanum oxide accounting for 4-7% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, nano-silica sol accounting for 3.5% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, and sodium dodecylbenzenesulfonate accounting for 6% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate are added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture is ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After thorough ball-milling, the mixture is washed with water and dried to obtain a calcium sulfate whisker modifier.

[0114] The irradiation power in the proton irradiation box of this embodiment is 225W.

[0115] The graphene negative ion water-based coating of this embodiment further includes 3.5 parts by weight of kaolin agent;

[0116] The preparation method of kaolin agent is:

[0117] S101: calcining kaolin at 300°C for 2 h, then cooling to 125°C at a rate of 3.5°C / min, holding for 20 min, and finally air-cooling to room temperature;

[0118] S102: The kaolin cooled to room temperature is mixed thoroughly with a sodium lignin sulfonate solution of 4 times the total amount of the kaolin, and then carboxymethyl cellulose of 12.5% ​​of the total amount of the kaolin and citric acid of 3.5% of the total amount of the kaolin are added and the mixture is further mixed thoroughly. Finally, the mixture is washed with water and dried to obtain a kaolin agent.

[0119] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 12.5%.

[0120] The preparation process of a graphene negative ion water-based coating of the present embodiment comprises the following steps: stirring and mixing the raw materials thoroughly to obtain the negative ion water-based coating of the present invention.

[0121] Comparative Example 1.

[0122] The difference from Example 3 is that no graphene liquid is added.

[0123] Comparative Example 2.

[0124] The difference from Example 3 is that SO1 treatment is not used in the graphene liquid.

[0125] Comparative Example 3.

[0126] The difference from Example 3 is that no conditioning agent is used in the graphene liquid.

[0127] Comparative Example 4.

[0128] The difference from Example 3 is that no nano-silica or silane coupling agent is added to the conditioning agent.

[0129] Comparative Example 5.

[0130] The difference from Example 3 is that no calcium sulfate whisker modifier is added to the conditioning agent.

[0131] Comparative Example 6.

[0132] The difference from Example 3 is that lanthanum oxide and nano-silica sol are not added in the preparation of the calcium sulfate whisker modifier.

[0133] Comparative Example 7.

[0134] The difference from Example 3 is that no kaolin agent was added.

[0135] Comparative Example 8.

[0136] The difference from Example 3 is that the kaolin agent is directly replaced by kaolin raw material.

[0137] The performance test results of Examples 1-3 and Comparative Examples 1-8 are as follows

[0138]

[0139]

[0140] From Examples 1-3 and Comparative Examples 1-8, it can be concluded that the product of Example 3 of the present invention can achieve coordinated improvements in the 72h antibacterial rate of Escherichia coli, antifouling performance, and purification adsorption. In the product without adding either the graphene liquid or the kaolin agent, the performance of the product deteriorates significantly. The two are used in combination to achieve synergistic effects.

[0141] The graphene liquid was not treated with SO1, the graphene liquid was not treated with a conditioning agent, nano-silica and silane coupling agent were not added to the conditioning agent, calcium sulfate whisker modifier was not added to the conditioning agent, and lanthanum oxide and nano-silica sol were not added during the preparation of the calcium sulfate whisker modifier. The performance of the products showed a trend of deterioration. The product raw materials obtained by the method of the present invention had the most significant performance effect. At the same time, the kaolin agent was directly replaced by kaolin raw materials, and the performance of the product also showed a trend of deterioration. The raw materials obtained by other methods were not as obvious as the effect of the present invention.

[0142] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

[0143] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A graphene negative ion water-based coating, characterized in that: The graphene negative ion water-based coating comprises the following raw materials in parts by weight: 5-10 parts of graphene liquid, 45-50 parts of negative ion stock solution, 175-185 parts of emulsion, 4-7 parts of auxiliary agent, 45-50 parts of pigment, 5-10 parts of nano silver powder, 5-10 parts of diatomaceous earth powder, 470-490 parts of deionized water and 2-5 parts by weight of kaolin agent; The negative ion stock solution is prepared by ball milling tourmaline powder, potassium tungstate powder and water in a weight ratio of 2:1:3 to obtain a negative ion stock solution; The preparation method of the graphene liquid is: S01: The graphene is first heat treated at 135-145°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at this temperature for 2 minutes, and finally cooled to 50°C at a rate of 1-3°C / min, and continued to be kept at this temperature; S02: 2-5 parts of nano-silicon dioxide, 1-3 parts of silane coupling agent and 2-5 parts of yttrium nitrate solution are fully mixed, and finally 1-2 parts of stearic acid and 0.25-0.35 parts of calcium sulfate whisker modifier are added in sequence, and stirred to obtain a conditioning agent; S03: The graphene and the conditioning agent kept warm in S01 are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a regulated graphene agent; S04: mixing the adjusted graphene agent, chitosan solution and phosphate buffer solution in a weight ratio of 3:5:1 to obtain a graphene solution; The preparation method of kaolin agent is: S101: calcining kaolin at 300°C for 2h, then cooling to 125°C at a rate of 2-5°C / min, keeping the temperature for 20min, and finally air cooling to room temperature; S102: The kaolin cooled to room temperature is mixed with a sodium lignin sulfonate solution which is 3-5 times the total amount of the kaolin, and then 10-15% of the total amount of the kaolin carboxymethyl cellulose and 2-5% of the total amount of the kaolin are added and mixed thoroughly, and finally washed with water and dried to obtain a kaolin agent.

2. A graphene anion water-based paint according to claim 1, characterized in that: The emulsion is an acrylic emulsion, and the solid content of the acrylic emulsion is 50%; The auxiliary agent is a wetting agent and a film-forming agent mixed in a weight ratio of 1:1, wherein the wetting agent is propylene glycol; the film-forming agent is glass cellulose; and the pigment is titanium dioxide.

3. A graphene negative ion water-based paint according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%; and the pH value of the phosphate buffer solution is 5.

5.

4. A graphene anion water-based paint according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH560.

5. A graphene anion water-based paint according to claim 1, characterized in that: The preparation method of the calcium sulfate whisker modifier is: The calcium sulfate whiskers are first irradiated in a proton irradiation box for 2-5 minutes. After the irradiation, the irradiated calcium sulfate whiskers are placed in 2-5 times the mass fraction of 5% sodium silicate solution and stirred evenly to obtain a calcium sulfate whisker agent adjusted by sodium silicate; Lanthanum oxide accounting for 4-7% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate, nano-silica sol accounting for 2-5% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate and sodium dodecylbenzene sulfonate accounting for 4-8% of the total amount of the calcium sulfate whisker agent adjusted by sodium silicate are added to the calcium sulfate whisker agent adjusted by sodium silicate, and the mixture is ball-milled at a ball-milling speed of 1500 r / min for 2 hours. The mixture is fully ball-milled, washed with water and dried to obtain a calcium sulfate whisker modifier.

6. A graphene anion water-based paint according to claim 5, characterized in that: The irradiation power in the proton irradiation box is 220-230W.

7. A graphene anion water-based paint according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 10-15%.

8. A process for preparing the graphene anion water-based coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials are stirred and mixed thoroughly to obtain the negative ion water-based paint.

Citation Information

Patent Citations

  • High-strength wear-resisting water-based paint

    CN107474659A

  • Lithium battery coating paint composition and method thereof

    CN117801637A